Different resource allocation strategies result from selection for litter size at weaning in rabbit does. (22nd January 2014) - Savietto, D.; Cervera, C.; Ródenas, L.; Martínez-Paredes, E.; Baselga, M.; García-Diego, F. J.; Larsen, T.; Friggens, N. C.; Pascual, J. J.
<x content-type="archive" xml:space="preserve">Abstract</x> This study examined the effect of long-term selection of a maternal rabbit line, solely for a reproductive criterion, on the ability of female rabbits to deal with constrained environmental conditions. Female rabbits from generations 16 and 36 (n=72 and 79, respectively) of a line founded and selected to increase litter size at weaning were compared simultaneously. Female rabbits were subjected to normal (NC), nutritional (NF) or heat (HC) challenging conditions from 1st to 3rd parturition. Animals in NC and NF were housed at normal room temperatures (18°C to 25°C) and respectively fed with control (11.6 MJ digestible energy (DE)/kg dry matter (DM), 126 g digestible protein (DP)/kg DM, and 168 g of ADF/kg DM) or low-energy fibrous diets (9.1 MJ DE/kg DM, 104 g DP/kg DM and 266 g ADF/kg DM), whereas those housed in HC were subjected to high room temperatures (25°C to 35°C) and the control diet. The litter size was lower for female rabbits housed in both NF and HC environments, but the extent and timing where this reduction took place differed between generations. In challenging conditions (NF and HC), the average reduction in the reproductive performance of female rabbits from generation 16, compared with NC, was −2.26 (P<0.05) and −0.51 kits born alive at 2nd and 3rd parturition, respectively. However, under these challenging conditions, the reproductive performance of female rabbits from generation 36 was less affected at 2nd parturition (−1.25 kits born alive), but showed a greater reduction at the 3rd parturition (−3.53 kits born alive; P<0.05) compared with NC. The results also showed differences between generations in digestible energy intake, milk yield and accretion, and use of body reserves throughout lactation in NC, HC and NF, which together indicate that there were different resource allocation strategies in the animals from the different generations. Selection to increase litter size at weaning led to increased reproductive robustness at the onset of an environmental constraint, but failure to sustain the reproductive liability when the challenge was maintained in the long term. This response could be directly related to the short-term environmental fluctuations (less severe) that frequently occur in the environment where this line has been selected.